Meningkatkan dan Mempertahankan Tingkat Layanan Prasarana Air - Sangkawati, Sri (Department of Civil Engineering, Diponegoro University, 2010)
The main problems of infrastructure in Indonesia, including infrastructure in the water sector is the shortage of funds for its construction, and infrastructure services need to be increased to compensate for population growth. Two of these are issues concerning the contradiction, so that one policy that needs to be taken is to maintain existing service levels and funds for operation and maintenance of infrastructure necessary to provide adequately, including by developing sources of funds derived from service contribution. Operations and maintenance funding sources to maintain the level of infrastructure services is charged to the user needs to be developed a good amount of acceptance and methods of calculating the contribution of each user. Methods for determining the allocation of funds to be charged to users who receive services from the infrastructure, can not be determined only by the quantity of water delivery for each purpose, but also based on the benefit of all water users. Keywords : hydraulic infrastructure, founding source for O&M, service charge Abstrak Permasalahan utama infrastruktur di Indonesia termasuk infrastruktur di sektor air adalah keterbatasan dana untuk pembangunannya, dan perlu peningkatan pelayanan sarana prasarana guna mengimbangi pertumbuhan jumlah penduduk. Dua hal tersebut merupakan permasalahan yang kontradiksi, sehingga salah satu kebijakan yang perlu ditempuh adalah mempertahankan tingkat pelayanan yang ada dan dana untuk operasi dan pemeliharaan prasarana perlu disediakan secara memadai, diantaranya dengan mengembangkan sumber dana yang berasal dari kontribusi pelayanan. Sumber dana operasi dan pemeliharaan untuk mempertahankan tingkat layanan prasarana yang dibebankan kepada pengguna perlu terus dikembangkan baik jumlah penerimaannya maupun metode perhitungan besarnya kontribusi masing-masing pengguna. Metode untuk menentukan besarnya alokasi dana yang akan dibebankan kepada kelompok pengguna yang menerima pelayanan dari prasarana keairan tidak dapat ditentukan hanya berdasarkan volume besarnya air saja., melainkan harus berdasarkan juga analsisis nilai manfaat dari seluruh penerima pelayanan prasarana keairan. Kata-kata Kunci : prasarana air, sumber dana O&P, jasa layanan